HEMOPHILIC INFECTION AMONG CHILDREN - A.G. Gaivoronskaya (Union of pediatricians of Russia, 2007)
The article highlights the problem of hemophilic infection among children, such as the recurrence of the carrier state, infection spread, diagnostics and treatment. The author clearly proves that the only reliable means for the specific prevention of this disease is the active immunization.Key words: hemophilic infection, vaccination, children.